Silver embedded porous carbon composite for high-performance lithium-metal anode - Dong Ki Kim; Joo Hyeong Suh; Yoojin Hong; Daeun Kim; Min-Sik Park; Jung Ho Kim (Science and Technology of Advanced Materials)
Using a lithium (Li) metal anode is essential for high-energy batteries, however, dendritic Li growth is unavoidable during Li plating and stripping processes. Strategically, a porous carbon structure derived from a metal-organic framework is suggested for directly storing metallic Li, although problems still exist with plating Li from the core to the surface and with stripping Li from the surface. Herein, we strategically utilize the carbon structure of zeolitic imidazolate framework-8 as an anode and replace the inactive residual Zn with Ag through galvanic displacement. The strong affinity of Ag for Li ions facilitates the transfer of plating from the surface of the carbon structure to its interior. After determining the optimal conditions for galvanic displacement by varying reaction times and temperatures, we carefully evaluate the electrochemical performance.